The impact of haemophilus influenzae type b (hib) vaccine on pneumonia and meningitis among children under the age of 1 year in the Klerksdorp district of the North West Province - Sebekedi ( Nee Mhele), Otsile, Calvinia (My University, 2000)
The purpose of this study was to determine the impact of Hib vaccine on pneumonia and meningitis in children under the age of 1 year in the Klerksdorp district of the North West Province.
Research report submitted to the Faculty of Health Sciences department of community health University of the Witwatersrand in partial fulfilment of the requirements of the degree in Master of Public Health
Keywords: Haemophilus influenzae; Haemophilus influenzae type b; Pneumonia; Meningitis; Child